Cooperation, Tax Complexity and Managerial Control: A Study on Tax Auditors' Conciliatory Style - Nordin, ZS; Muhammad, I; Abd Wahab, K; Yaakub, NA (Univ Malaya, Fac Business & Accountancy, 2024)
Manuscript type: Research paper. Research aim: This paper aims to investigate the external factors that influence tax auditors' conciliatory style when dealing with tax disputes. Design/ Methodology/ Approach: A self-administered questionnaire which serves as the research instrument was used in this study. Respondents were tax auditors attached to the Inland Revenue Board of Malaysia (IRBM) in Peninsular Malaysia. Research findings: Findings show that the external factors of tax complexity and managerial control significantly influence tax auditors' conciliatory style. However, taxpayers' cooperation carries no impact. Theoretical contribution/ Originality: This study provides empirical evidence which demonstrates the influence of external factors (such as taxpayers' cooperation, tax complexity and managerial control) on tax auditors' conciliatory style. Practitioner/ Policy implications: The findings are relevant to the IRBM who can use the outcome to improve its dispute resolution process as well as to gain a better understanding of tax auditors' behaviour. Research limitation/ Implication: The findings of this study can only be generalised to the population in Peninsular Malaysia. Thus, future studies may be conducted in East Malaysia and other Asian countries so as to examine if tax auditors' behaviour differs across cultures.